2010
DOI: 10.1086/651197
|View full text |Cite
|
Sign up to set email alerts
|

A Student in Distress: Moral Frames and Bystander Behavior in School

Abstract: The purpose of this study was to investigate and generate a grounded theory on how and why students behave as they do in school situations in which they witness another student in distress. Fieldwork and interviews were conducted in 2 Swedish elementary schools and guided by a grounded theory approach. The study resulted in a grounded theory of moral frames in bystander situations in school. In this study, 5 main moral frames of school have been identified: (a) the moral construction of the good student, (b) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 42 publications
6
43
1
1
Order By: Relevance
“…As found in previous studies (Thornberg, 2010;Thornberg et al, 2012), the degree to which students define harm in the situation influences their motivation to intervene or not intervene. Not all situations are defined as serious or as bullying.…”
Section: Defining the Seriousnessmentioning
confidence: 54%
See 3 more Smart Citations
“…As found in previous studies (Thornberg, 2010;Thornberg et al, 2012), the degree to which students define harm in the situation influences their motivation to intervene or not intervene. Not all situations are defined as serious or as bullying.…”
Section: Defining the Seriousnessmentioning
confidence: 54%
“…Different methods have been used, such as open questions in questionnaires (Bellmore, Ma, You, & Hughes, 2012;Rigby & Johnson, 2005), field observations and follow-up interviews (Thornberg 2007(Thornberg , 2010, and qualitative interviews .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas boys play and interact in larger groups and establish and maintain friendships based on mutual interests and activities, girls form close, intimate friendship relationships in which they more typically share confidences (Golombok and Fivush 1994). Being sensitive, empathic, affectionate, intimate, and interested in emotional issues is more in line with traditional female identity and norms and less with male identity and norms (e.g., Maccoby and Jacklin 1987;Thornberg 2010a;Thorne 1993). For example, Tracey et al (2005) found that female adolescents were more interested in social issues than male adolescents.…”
Section: Discussionmentioning
confidence: 99%